A challenging topic of computer simulations: Polymorphism in polymers. Issue 2 (10th March 2020) - Luo, Chuanfu
Abstract: To predict crystalline structures and respective mechanic properties of polymers are the long‐term target of computer simulations. The simulation of polymorphism in polymers requires the all‐atom model with proper force field. The all‐atom model can provide correct crystalline structure and the respective properties, but results in extremely slow dynamics in simulations. The conventional molecular dynamics (MD) using the all‐atom model could be applied to the study of polymorphism of simple polymers without side chain groups such as polyethylene. For more complex polymers with side chain groups, the conventional MD using the all‐atom models are too slow and accelerating methods must be used to boost the slow chain dynamics. The metadynamics and hybrid dynamics might be used in the future simulations of polymorphism. Abstract : Computer simulation of polymorphism in polymers is a challenging topic. The all‐atom model must be used to obtain correct crystalline structures and respective properties. The conventional molecular dynamics simulations are very slow using the all‐atom model, excepting some simple polymers without side chain groups such as polyethylene and polyvinylidene difluoride. The future advances in polymorphism simulations might be based on accelerating algorithms such as metadynamics and hybrid dynamics.